2016
DOI: 10.1071/sp16002
|View full text |Cite
|
Sign up to set email alerts
|

Upper atmospheric remote sensing using ELF – VLF lightning generated tweek and whistler sferics

Abstract: Tweek and whistler atmospherics (sferics)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 27 publications
0
0
0
Order By: Relevance
“…YanPing et al [4] studied the frequency and dispersion characteristics of whistler waves, through the detection of low-frequency emission originating from natural and artificial activities by the high-quality WHU ELF/VLF receiver system deployed in Suizhou, China. Kishore et al [5] probed the D-region of the ionosphere in the nighttime and the plasmasphere by recording tweek-and whistler-wave atmospherics recorded at a low latitude station, the Suva in the South Pacific region. Zahlava et al [6] found that waves in the ionosphere were strongly related to frequency and geomagnetic latitude by analyzing the measurements from the detection of electro-magnetic emissions transmitted from spacecraft from earthquake regions.…”
Section: Introductionmentioning
confidence: 99%
“…YanPing et al [4] studied the frequency and dispersion characteristics of whistler waves, through the detection of low-frequency emission originating from natural and artificial activities by the high-quality WHU ELF/VLF receiver system deployed in Suizhou, China. Kishore et al [5] probed the D-region of the ionosphere in the nighttime and the plasmasphere by recording tweek-and whistler-wave atmospherics recorded at a low latitude station, the Suva in the South Pacific region. Zahlava et al [6] found that waves in the ionosphere were strongly related to frequency and geomagnetic latitude by analyzing the measurements from the detection of electro-magnetic emissions transmitted from spacecraft from earthquake regions.…”
Section: Introductionmentioning
confidence: 99%